PERBANDINGAN TINGKAT KESEHATAN BANK ANTARA BNI DAN BCA DILIHAT DARI FAKTOR RENTABILITAS PERIODE 2017-2021 - Maria, Mayrisa Styaningrum; Savitri Kusmargiani, Ida; Yudha Kusuma, Septian (Indonesian Journal of Business Economics and Management, 2022)
This study aims to analyze the assessment and find out the comparison between the health levels ofBNI and BCA in terms of profitability. The type of research in this study is comparative descriptiveresearch with quantitative and qualitative approaches. The sources of data in this study aresecondary data obtained through the financial statements of BNI and BCA. The research methodused is based on the assessment of the profitability factor in accordance with the Circular Letter ofthe Financial Services Authority Number 14/SEOJK.03/2017 concerning the Health Assessment ofCommercial Banks, which consists of an assessment of the bank's performance in generating profits(profitability), sources that support profitability, stability ( sustainability) components that supportprofitability, as well as profitability management. Hypothesis testing using the Mann Whitney U-TestSPSS 25. The results of the profitability assessment at BNI and BCA during the 2017–2021 periodshowed very adequate results. Then the results of the comparison of health levels show that there isa significant difference between BNI and BCA, with the result that BCA has a higher value than BNI